2002
DOI: 10.1073/pnas.252603099
|View full text |Cite
|
Sign up to set email alerts
|

Persistent millennial-scale shifts in moisture regimes in western Canada during the past six millennia

Abstract: Inferences of past climatic conditions from a sedimentary record from Big Lake, British Columbia, Canada, over the past 5,500 years show strong millennial-scale patterns, which oscillate between periods of wet and drier climatic conditions. Higher frequency decadal-to centennial-scale fluctuations also occur within the dominant millennial-scale patterns. These changes in climatic conditions are based on estimates of changes in lake depth and salinity inferred from diatom assemblages in a well dated sediment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…For example, diatom inferences from British Columbia (western Canada) show a distinct shift to drier conditions and lower water levels ca. A.D. 700 (32). In addition, this shift corresponds closely to a sharp decline in ice-rafting debris in the North Atlantic ca.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, diatom inferences from British Columbia (western Canada) show a distinct shift to drier conditions and lower water levels ca. A.D. 700 (32). In addition, this shift corresponds closely to a sharp decline in ice-rafting debris in the North Atlantic ca.…”
Section: Discussionmentioning
confidence: 68%
“…Together, these patterns suggest that some large-scale climatic shifts may be a common phenomenon, which may reoccur over longer time frames. For example, millennial-scale shifts over at least the past 5,500 years, between sustained periods of wetter and drier conditions, occurring approximately every 1,220 years, have been reported from western Canada (32). The striking correspondence of these shifts to large changes in fire frequencies, inferred from two sites several hundreds of kilometers to the southwest in the mountain hemlock zone of southern British Columbia (39), suggests that these millennial-scale dynamics are linked and operate over wide spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…This signal appears less marked in the tropics (Horn and Sanford 1992;Turcq et al 1998) and in other mid-latitude regimes, such as in eastern Canada (Carcaillet et al 2001) and New Zealand (Molloy et al 1963). Cumming et al (2002) reported on persistent millennial-scale effects on moisture availability recorded at Big Lake, BC, in the semi-arid Cariboo region, some 500 km south of the Bear Lake site. It is also important to note recent studies, such as those of cyclic variations in an Alaskan lake, reported by Hu et al (2003), which suggest millennial-scale periodicity.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that during the Holocene the climate of Pacific North America (PNAM) underwent periodic regime shifts (Bond et al 1997;Cumming et al 2002) and that these shifts were reflected in glacial mass balance adjustments throughout the western North American cordillera (Denton and Karlén 1973;Dyurgerov and Meier 2000). There is currently considerable interest in reconstructing the timing and extent of alpine glacier fluctuations and associated mass balance adjustments throughout the Holocene as a means to place ongoing climatic changes into a longer temporal context.…”
Section: Introductionmentioning
confidence: 99%